New Polygordiidae (Polychaeta) from the Australian region - Avery, Lynda; Ramey, Patricia A.; Wilson, Robin S. (Zootaxa, 2009)
The interstitial polychaete family Polygordiidae is recorded from Australia for the first time, based on two new species: Polygordius arafura sp. nov. from continental shelf depths in the Arafura Sea, northern Australia, and Polygordius kiarama sp. nov. from the continental shelf and slope off southeastern Australia. Polygordius kiarama sp. nov., found at slope depths up to 1650 m, is the deepest record to date for the family, which has previously been recorded from intertidal habitats, shallow coastal waters and continental shelf depths.